Sensor design strategy for environmental and biological monitoring. Issue 5 (15th February 2023) - Heo, Jun Hyuk; Sung, Minchul; Trung, Tran Quang; Lee, Yullim; Jung, Do Hyeon; Kim, Hajeong; Kaushal, Sandeep; Lee, Nae‐Eung; Kim, Jin Woong; Lee, Jung Heon; Cho, Soo‐Yeon
Abstract: Rapid industrial growth has severely impacted ecosystems and aggravated economic and health risks to society. Monitoring of ecosystems is fundamental to our understanding of how ecosystem change impacts resources and is critical for developing data‐based sustainability. Thus, the design and development of optimized sensors for ecosystem monitoring have received increasing attention. This review provides a comprehensive overview of systematic sensor design strategies for ecosystem monitoring from the material level to the form factor level. We discuss the fundamental transducing mechanisms of a representative sensor system including optical, electrical, and electrochemical sensors. We then review the sensor interfacing strategy for achieving stable and real‐time monitoring of environmental biochemical factors from air, water, soil, and living organisms. Finally, we provide a summary of the current performance and prospects of this state‐of‐the‐art sensor technology and an outlook on opportunities for possible future research directions in this emerging field. Abstract : This review systematically presents the sensor design strategies, namely optical, electrical, and electrochemical sensor for efficient ecosystem monitoring including air, water, soil, and living organisms. We hope that readers that be able to predict the performance that will be achieved by combining certain sensors in advance based on this information.